Carbon nanotube-based triode field emission lamps using metal meshes with spacers - Cho, Woo-Sung; Lee, Hyeon-Jae; Lee, Yang-Doo; Park, Jung-Ho; Kim, Jai-Kyeong; Lee, Yun-Ili; Ju, Byeong-Kwon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
We fabricated a carbon nanotube (CNT)-based triode field emission flat lamp with a gated emitter structure, which is composed of a metal grid with a spacer as a gate, a cathode electrode layer, and a CNT layer. The metal mesh was designed with trenches and numerous holes to make a gap between gate and cathode electrodes and to provide electrons with a highly efficient passage. We observed that this metal mesh decreased the vibration and leakage current owing to high electric field generated from anode. As a result, the uniformity and stability of this field emission lamp was improved.